Characterization of atypical T cells generated during ex vivo expansion process for T cell-based adoptive immunotherapy - Mercier-Letondal, Patricia; Kumar, Abhishek; Marton, Chrystel; Bonnefoy, Francis; Fredon, Maxime; Boullerot, Laura; Dehecq, Barbara; Adotévi, Olivier; Godet, Yann; Galaine, Jeanne (Frontiers in Immunology, 2024)
Engineered T cell-based adoptive immunotherapies met promising success for the treatment of hematological malignancies. Nevertheless, major hurdles remain to be overcome regarding the management of relapses and the translation to solid tumor settings. Properties of T cell-based final product should be appropriately controlled to fine-tune the analysis of clinical trial results, to draw relevant conclusions, and finally to improve the efficacy of these immunotherapies. For this purpose, we addressed the existence of atypical T cell subsets and deciphered their phenotypic and functional features in an HPV16-E7 specific and MHC II-restricted transgenic-TCR-engineered T cell setting. To note, atypical T cell subsets include mismatched MHC/co-receptor CD8 or CD4 and miscommitted CD8+ or CD4+ T cells. We generated both mismatched and appropriately matched MHC II-restricted transgenic TCR on CD8 and CD4-expressing T cells, respectively. We established that CD4+ cultured T cells exhibited miscommitted phenotypic cytotoxic pattern and that both interleukin (IL)-2 or IL-7/IL-15 supplementation allowed for the development of this cytotoxic phenotype. Both CD4+ and CD8+ T cell subsets, transduced with HPV16-E7 specific transgenic TCR, demonstrated cytotoxic features after exposure to HPV-16 E7-derived antigen. Ultimately, the presence of such atypical T cells, either mismatched MHC II-restricted TCR/CD8+ T cells or cytotoxic CD4+ T cells, is likely to influence the fate of patient-infused T cell product and would need further investigation.